Polyimide binder precursor composition and power storage device using same

JP7639950B2Active Publication Date: 2025-03-05UBE CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023575268
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-01-18
Publication Date
2025-03-05
Estimated Expiration
2043-01-18

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、不可逆容量が小さいポリイミドバインダおよびその前駆体組成物を提供することができる。また、本発明のポリイミドバインダを使用することで、初期充放電効率が高いリチウムイオン二次電池等の蓄電デバイスを提供できる。このポリイミドバインダを例えば負極バインダとして用いると、不可逆容量を補填する正極側の活物質量を低減することができ、その結果、軽量で高容量の蓄電デバイスを得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639950000018
    Figure 0007639950000018
  • Figure 0007639950000001
    Figure 0007639950000001
  • Figure 0007639950000002
    Figure 0007639950000002
Patent Text Reader

Abstract

Provided is a polyimide binder from which a high-capacity power storage device, which has a small irreversible capacity and a high initial charge-discharge efficiency and is lightweight, can be obtained. This polyimide binder precursor composition is a polyimide binder precursor composition for a power storage device electrode, and includes a reaction product of a tetracarboxylic acid component and a diamine component, and a solvent. A polyimide binder obtained from said polyimide binder precursor composition has an irreversible capacity of at most 1,200 mAh / g.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide-based binder for electricity storage devices such as lithium ion secondary batteries, and more particularly to a polyimide binder precursor composition, an electrode mixture paste, a negative electrode active material layer, a negative electrode sheet, and an electricity storage device. [Background technology]

[0002] Lithium-ion secondary batteries and other power storage devices have a high energy density and high capacity, and are therefore widely used as power sources for mobile information terminals. In recent years, industrial applications, such as installation in electric and hybrid vehicles and unmanned aerial vehicles, have been considered, and efforts are being made to further increase the capacity of lithium-ion secondary batteries and other power storage devices. As an example of increasing capacity, studies are being conducted on increasing the charge and discharge capacity of the negative electrode by using silicon or tin, which have a large lithium absorption capacity per unit volume, or alloys containing these.

[0003] However, it is known that electrode active materials with large charge / discharge capacities, such as silicon, tin, or alloys containing these, undergo a very large volume change during charging and discharging. Therefore, when these electrode active materials are used to form a negative electrode active material layer with a general-purpose binder such as polyvinylidene fluoride or a rubber-based resin, the negative electrode active material layer suffers from layer destruction or interfacial peeling between the current collector and the negative electrode active material layer due to the volume change of the electrode active material, resulting in a problem of reduced cycle characteristics of electricity storage devices such as lithium ion secondary batteries.

[0004] To address these problems, the use of polyimide-based binders has been proposed as a method for improving the deterioration of cycle characteristics caused by volume changes during repeated charging and discharging (see, for example, Patent Documents 1 to 3).

[0005] On the other hand, Patent Document 4 (US2006 / 0099506) points out that a large irreversible capacity is observed when a polyimide-based binder is used. Specifically, Patent Document 4 proposes a solution to reduce the irreversible capacity by replacing a part or all of the tetracarboxylic acid dianhydride in a polyimide-based binder obtained from 3,3'4,4'-benzophenonetetracarboxylic acid dianhydride and 4,4'-oxydianiline with 1,2,3,4-butanetetracarboxylic acid dianhydride, which is a chain aliphatic tetracarboxylic acid dianhydride.

[0006] In addition, Patent Document 5 (JP 2019-3873 A) describes the use of a binder containing an imide group-containing polymer compound having a tensile modulus of elasticity of 3.0 GPa or more and a reactivity to lithium ions of 1200 mAh / g or less in a negative electrode active material layer containing a silicon-based negative electrode active material. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2013 / 035806 [Patent Document 2] International Publication No. 2017 / 022796 [Patent Document 3] International Publication No. 2018 / 174299 [Patent Document 4] US2006 / 0099506 publication [Patent Document 5] JP 2019-3873 A Summary of the Invention [Problem to be solved by the invention]

[0008] The inventors have found that if the binder itself has an irreversible capacity, Li is also taken in the binder during the initial charge, and Li that is not released during discharge remains in the binder, so it is assumed that Li greater than the theoretical capacity of the negative electrode active material is required. Therefore, the larger the irreversible capacity of the binder itself, the more Li must be loaded on the positive electrode, and there is a concern that the weight of the entire battery will increase. In order to eliminate such concerns, the development of a polyimide-based binder with a smaller irreversible capacity is required. As described above, Patent Document 4 aims to reduce the irreversible capacity, but the degree of reduction is insufficient and no compositional consideration has been made. In addition, Patent Document 5 suggests that the reactivity to lithium ions is related to cycle characteristics, but it does not measure the initial irreversible capacity. In order to correctly evaluate the effect on the initial efficiency, it is necessary to evaluate the charge / discharge capacity of the binder itself and grasp the irreversible capacity, which is the difference between them. In addition, there is almost no mention of the structure of the polyimide, so it is not possible to grasp the details.

[0009] In addition, in the case of a lithium ion capacitor, if the irreversible capacity of the binder is large, a large amount of lithium ions will be required for pre-doping, and it is expected that the pre-doping processing time, etc. will change significantly.

[0010] The present invention aims to solve the above problems and provides a polyimide binder and a precursor composition thereof having a small irreversible capacity. In addition, by using the polyimide binder of the present invention, it is possible to provide an electricity storage device such as a lithium ion secondary battery having a high initial charge / discharge efficiency. [Means for solving the problem]

[0011] The present invention relates to the following items. 1. A polyimide binder precursor composition for an electrode of an electrical storage device, comprising a reaction product of a tetracarboxylic acid component and a diamine component, and a solvent, A polyimide binder precursor composition, wherein the irreversible capacity of a polyimide binder obtained from the polyimide binder precursor composition is 1200 mAh / g or less.

[0012] 2. The polyimide binder precursor composition according to item 1, wherein the polyimide binder precursor composition comprises a reaction product of a tetracarboxylic acid component containing 50 mol % or more of an alicyclic tetracarboxylic acid dianhydride and a diamine component, and a solvent.

[0013] 3. The polyimide binder precursor composition according to item 1 or 2 above, wherein the diamine component contains 50 mol % or more of an aromatic diamine compound.

[0014] 4. A negative electrode mixture paste for an electricity storage device, comprising the polyimide binder precursor composition according to any one of items 1 to 3 above, and an active material containing a silicon-containing material and / or graphite.

[0015] 5. (a) an active material comprising a silicon-containing material and / or graphite; and A heat-treated product of the polyimide precursor contained in the polyimide binder precursor composition according to any one of items 1 to 3, comprising a polyimide binder that binds the active material. A negative electrode active material layer containing (b) Current collector A negative electrode for an electricity storage device comprising:

[0016] 6. An electricity storage device comprising the electricity storage device negative electrode according to item 5 above.

[0017] 7. A step of casting or applying the negative electrode mixture paste according to item 4 on a current collector; A process of heating the applied layer of negative electrode mixture paste to form a negative electrode active material layer. The method for producing a negative electrode for an electricity storage device comprising the steps of:

[0018] 8. A method for producing an electricity storage device, comprising the method for producing a negative electrode according to item 7 as one step. Effect of the Invention

[0019] According to the present invention, it is possible to provide a polyimide binder having a small irreversible capacity and a precursor composition thereof. In addition, by using the polyimide binder of the present invention, it is possible to provide an electricity storage device such as a lithium ion secondary battery having a high initial charge / discharge efficiency. When this polyimide binder is used as, for example, a negative electrode binder, it is possible to reduce the amount of active material on the positive electrode side that compensates for the irreversible capacity, and as a result, it is possible to obtain a lightweight, high-capacity electricity storage device. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a diagram showing one embodiment of a method for calculating the irreversible capacity of a polyimide binder itself in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The polyimide binder precursor composition of the present invention contains a reaction product of a tetracarboxylic acid component and a diamine component, and a solvent. The reaction product of the tetracarboxylic acid component and the diamine component in the polyimide binder precursor composition is a polyimide precursor as described below. The polyimide binder precursor composition of the present invention can be converted into a polyimide binder that binds particles of an active material, for example, by heating the polyimide binder precursor composition of the present invention together with particles of an active material, for example, to remove the solvent, and then subjecting the polyimide binder precursor composition to an imidization reaction as necessary. Therefore, in the present invention, the "polyimide binder (of the present invention)" is a binder obtained from the polyimide binder precursor composition of the present invention, and is a substance that binds particles of an active material, for example, in an electrode.

[0022] The polyimide binder obtained from the polyimide binder precursor composition of the present invention has an irreversible capacity of 1200 mAh / g or less, preferably 1100 mAh / g or less, more preferably 1000 mAh / g or less, even more preferably 900 mAh / g or less, and even more preferably 800 mAh / g or less.

[0023] The irreversible capacity of the polyimide binder can be determined as follows. (1) A polyimide binder precursor composition and a negative electrode active material are mixed in different ratios to produce a plurality of mixture pastes for evaluation. The mixture pastes for evaluation are used to produce a plurality of negative electrodes for evaluation having different polyimide binder contents. (2) For example, the initial charge capacity and initial discharge capacity of the negative electrode for evaluation are measured using metallic lithium as the counter electrode, and the difference between the charge capacity (mAh / g) and discharge capacity (mAh / g) of the active material layer is taken as the irreversible capacity (mAh / g) of the negative electrode for evaluation. Here, the charge capacity and discharge capacity per unit mass are calculated based on the total mass of the active material and binder. (3) The irreversible capacity (mAh / g) of the evaluation negative electrode is plotted against the polyimide binder content (mass%) to prepare a calibration curve. The irreversible capacity of the evaluation negative electrode with a polyimide binder content of 100% is defined as the "irreversible capacity of the polyimide binder."

[0024] The negative electrode active material for producing the evaluation negative electrode does not need to be a silicon-based material, and it is preferable to use graphite, which has a smaller capacity than silicon-based materials. In addition, the counter electrode is preferably made of metallic lithium in order to eliminate the influence of the irreversible capacity of the counter electrode.

[0025] It is also preferable that the polyimide binder has excellent mechanical properties. A binder with excellent mechanical properties can withstand expansion and contraction accompanying charge and discharge even when a material that undergoes a large volume change, such as a silicon-based material, is used as the electrode active material, and is therefore known to prevent the active material from falling off and to have excellent cycle characteristics. The mechanical properties of the polyimide binder can be measured using a polyimide film formed from the polyimide binder precursor composition. A representative mechanical property is the elastic modulus, which is preferably 1.0 GPa or more, more preferably 2.0 GPa or more, and even more preferably 2.5 GPa or more. It is also preferable that the elongation percentage (elongation at break) is large, specifically, preferably 30% or more, more preferably 40% or more, even more preferably 50% or more, even more preferably 60% or more, and even more preferably 70% or more. The breaking energy is preferably 40 MJ / m 3 More than 50MJ / m 3 More preferably, 60MJ / m 3 That's all. In particular, it is preferred that the elastic modulus, elongation (elongation at break) and breaking energy all simultaneously fall within the "preferred" range.

[0026] Next, the components of the polyimide binder precursor composition and the production method thereof will be described.

[0027] <Reaction product of tetracarboxylic acid component and diamine component> In this specification, the tetracarboxylic acid component includes tetracarboxylic acid, tetracarboxylic dianhydride, and other tetracarboxylic acid derivatives such as tetracarboxylic acid silyl ester, tetracarboxylic acid ester, and tetracarboxylic acid chloride, which are used as raw materials for producing polyimide. Although not particularly limited, it is convenient to use tetracarboxylic dianhydride in production, and an example in which tetracarboxylic dianhydride is mainly used as the tetracarboxylic acid component will be described. In addition, the diamine component is a diamine compound having two amino groups (-NH2) which is used as a raw material for producing polyimide.

[0028] Here, the reaction product between the tetracarboxylic acid component and the diamine component is usually called a polyimide precursor, and typically contains a polyamic acid (or a derivative thereof) whose repeating unit is represented by the following general formula (I), but may also have a structure in which imidization has progressed further: In the formula, X1 is derived from the tetracarboxylic acid component, and Y1 is derived from the diamine component.

[0029] [ka] (In general formula I, X1 is a tetravalent aliphatic or aromatic group, Y1 is a divalent aliphatic or aromatic group, and R1 and R2 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms.)

[0030] The repeating unit of general formula (I) which is further imidized is a structure in which one or two of the two amide bonds present in general formula (I) are converted to imide bonds, and specifically, the repeating unit of general formulae (Ib), (Ic), and (II) below:

[0031] [ka]

[0032] [ka]

[0033] [ka] As shown in the figure.

[0034] When all the repeating units in the polyimide precursor are of general formula (I), the imidization rate is 0%, when all the repeating units are of general formula (Ib) and / or (Ic), the imidization rate is 50%, and when all the repeating units are of general formula (II), the imidization rate is 100% (i.e., polyimide). The imidization rate of the polyimide precursor may be in any range from 0 to 100%. In the present application, even if the imidization rate is 100%, one present in the polyimide binder precursor composition is referred to as a polyimide precursor.

[0035] In a preferred embodiment, the repeating unit of formula (I) may be included, and may contain repeating units selected from formulas (I), (Ib) and / or (Ic), and formula (II) so that the imidization rate is, for example, 0 to 50%, for example, 0 to 30%, or even 0 to 20%. In another embodiment, the repeating unit of formula (II) may be included, and may contain repeating units selected from the above formulas so that the imidization rate is, for example, more than 50% to 100%.

[0036] As the tetracarboxylic acid component, an aliphatic tetracarboxylic dianhydride or an aromatic tetracarboxylic dianhydride is used. As the aliphatic tetracarboxylic dianhydride, an alicyclic tetracarboxylic dianhydride is preferable, for example, a dianhydride of a tetracarboxylic acid in which four carboxyl groups are directly bonded to an alicyclic group X1 is preferable. By using a cyclic tetracarboxylic dianhydride, it is possible to achieve both high capacity of the electricity storage device by reducing the irreversible capacity of the polyimide binder and mechanical strength.

[0037] In a preferred embodiment of the present invention, the proportion of alicyclic tetracarboxylic dianhydrides in the total tetracarboxylic acid components is 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, and even more preferably 80 mol % or more (including 100 mol %). The remaining tetracarboxylic acid components are preferably aromatic tetracarboxylic dianhydrides.

[0038] When the polyimide precursor is obtained using a tetracarboxylic acid component containing an alicyclic tetracarboxylic dianhydride and another tetracarboxylic dianhydride (preferably an aromatic tetracarboxylic dianhydride), the form of the polyimide precursor does not matter, whether it is a copolymer, a block (co)polymer, a homopolymer blend, or a copolymer and homopolymer blend. A copolymer has an alicyclic group X1 and an aromatic group X1 in one molecule, a block (co)polymer has one molecule formed by reacting a block of repeating units of an alicyclic group X1 with a block of repeating units of an aromatic group X1, and a homopolymer blend is a blend of a polymer having only an alicyclic group X1 and a polymer having only an aromatic group X1.

[0039] Regarding the alicyclic tetracarboxylic dianhydride, the alicyclic group X1 is preferably a tetravalent group having an alicyclic structure with 4 to 40 carbon atoms, and more preferably has at least one aliphatic 4- to 12-membered ring, more preferably an aliphatic 4-membered ring or an aliphatic 6-membered ring. Preferable tetravalent groups having an aliphatic 4-membered ring or an aliphatic 6-membered ring include the following.

[0040] [ka] (In the formula, R 31 ~R 38 R is independently a direct bond or a divalent organic group. 41 ~R 47 , and R 71 ~R 73 R each independently represents one selected from the group consisting of groups represented by the formulas: -CH2-, -CH=CH-, -CH2CH2-, -O-, and -S-. 48 is an organic group containing an aromatic ring or an alicyclic structure.

[0041] R 31 , R 32 , R 33 , R 34 , R 35 , R 36 , R37 , R 38 Specific examples of the bond include a direct bond, an organic group containing an aromatic ring or an alicyclic structure, an aliphatic hydrocarbon group having 1 to 6 carbon atoms, an oxygen atom (-O-), a sulfur atom (-S-), a carbonyl bond, an ester bond, and an amide bond.

[0042] R 31 ~R 38 or R 48 Examples of the organic group containing an aromatic ring as the aromatic ring include the following.

[0043] [ka] (Wherein, W1 is a direct bond or a divalent organic group, n 11 ~n 13 each independently represents an integer of 0 to 4; R 51 , R 52 , R 53 are each independently an alkyl group having 1 to 6 carbon atoms, a halogen group, a hydroxyl group, a carboxyl group, or a trifluoromethyl group.

[0044] Specific examples of W1 include a direct bond, a divalent group represented by the following formula (5), and a divalent group represented by the following formula (6).

[0045] [ka] (R in Equation (6) 61 ~R 68 each independently represents a direct bond or a divalent group represented by the formula (5).

[0046] As the tetravalent group having an alicyclic structure, the following are particularly preferred.

[0047] [ka]

[0048] Examples of the alicyclic tetracarboxylic dianhydride include monocyclic alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutanetetracarboxylic dianhydride and cyclohexane-1,2,4,5-tetracarboxylic dianhydride, [1,1'-bi(cyclohexane)]-3,3',4,4'-tetracarboxylic dianhydride, [1,1'-bi(cyclohexane)]-2,3,3',4'-tetracarboxylic dianhydride, and [1,1'-bi(cyclohexane)]- 2,2',3,3'-Tetracarboxylic dianhydride, 4,4'-methylenebis(cyclohexane-1,2-dicarboxylic anhydride), 4,4'-(propane-2,2-diyl)bis(cyclohexane-1,2-dicarboxylic anhydride), 4,4'-oxybis(cyclohexane-1,2-dicarboxylic anhydride), 4,4'-thiobis(cyclohexane-1,2-dicarboxylic anhydride), 4,4'-sulfonylbis(cyclohexane-1,2-dicarboxylic anhydride) anhydride), 4,4'-(dimethylsilanediyl)bis(cyclohexane-1,2-dicarboxylic anhydride), 4,4'-(tetrafluoropropane-2,2-diyl)bis(cyclohexane-1,2-dicarboxylic anhydride), octahydropentalene-1,3,4,6-tetracarboxylic dianhydride, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic dianhydride, 6-(carboxymethyl)bicyclo[2.2.1]heptane-2 ,3,5-tricarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]oct-5-ene-2,3,7,8-tetracarboxylic dianhydride, tricyclo[4.2.2.02,5]decane-3,4,7,8-tetracarboxylic dianhydride, tricyclo[4.2.2.02,5]dec-7-ene-3,4,9,10-tetracarboxylic dianhydride, 9-oxatricyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic dianhydride, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride, (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethanonaphthalene-2c,3c,6c,7c-tetracarboxylic dianhydride, (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethanonaphthalene-2c,3c,6c,7c-tetracarboxylic dianhydride Examples of the alicyclic tetracarboxylic dianhydrides include t,4t:5c,8c-dimethanonaphthalene-2t,3t,6c,7c-tetracarboxylic dianhydride, decahydro-1,4-ethano-5,8-methanonaphthalene-2,3,6,7-tetracarboxylic dianhydride, and tetradecahydro-1,4:5,8:9,10-trimethanoanthracene-2,3,6,7-tetracarboxylic dianhydride. These may be used alone or in combination.

[0049] The aromatic tetracarboxylic dianhydride preferably has 2 to 3 aromatic rings. Examples of the aromatic group X1 include compounds having the following structures.

[0050] [ka] (In the formula, Z1 is a direct bond or the following divalent group:

[0051] [ka] In the formula, Z2 is a divalent organic group, Z3 and Z4 are each independently an amide bond, an ester bond, or a carbonyl bond, and Z5 is an organic group containing an aromatic ring.

[0052] Specific examples of Z2 include aliphatic hydrocarbon groups having 2 to 24 carbon atoms and aromatic hydrocarbon groups having 6 to 24 carbon atoms.

[0053] Specific examples of Z5 include aromatic hydrocarbon groups having 6 to 24 carbon atoms.

[0054] Examples of aromatic tetracarboxylic dianhydrides include, but are not limited to, halogen-unsubstituted aromatic tetracarboxylic dianhydrides such as 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, diphenylsulfonetetracarboxylic dianhydride, p-terphenyltetracarboxylic dianhydride, and m-terphenyltetracarboxylic dianhydride; 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride, 5,5'-[2,2,2-trifluoroisopropylidene] ... Preferred examples of the halogen-substituted tetracarboxylic acid dianhydrides include tetracarboxylic acid dianhydrides such as 1-[3-(trifluoromethyl)phenyl]ethylidene]diphthalic anhydride, 5,5'-[2,2,3,3,3-pentafluoro-1-(trifluoromethyl)pyropyridene]diphthalic anhydride, 1H-difuro[3,4-b:3',4'-i]xanthene-1,3,7,9(11H)-tetrone, 5,5'-oxybis[4,6,7-trifluoro-pyromellitic anhydride], 3,6-bis(trifluoromethyl)pyromellitic dianhydride, 4-(trifluoromethyl)pyromellitic dianhydride, 1,4-difluoropyromellitic dianhydride, and 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorobenzene dianhydride. These may be used alone or in combination.

[0055] As the diamine component, an aromatic diamine compound or an aliphatic diamine compound is used. In a preferred embodiment of the present invention, the proportion of the aromatic diamine compound in the total diamine components is 50 mol% or more, more preferably 60 mol% or more, even more preferably 70 mol% or more, and even more preferably 80 mol% or more (including 100 mol%). The remaining diamine components are aliphatic diamine compounds, preferably diamine compounds having an alicyclic structure. In a different embodiment, the diamine component may contain an aliphatic diamine compound, preferably an alicyclic diamine compound, in the total diamine components at a proportion of 50 mol% or more, more preferably 60 mol% or more, even more preferably 70 mol% or more, and even more preferably 80 mol% or more (including 100 mol%).

[0056] Regarding the aromatic diamine compound, examples of the aromatic group Y1 include the following.

[0057] [ka] (Wherein, W1 is a direct bond or a divalent organic group, n 11 ~n 13 each independently represents an integer of 0 to 4; R 51 , R 52 , R 53 are each independently an alkyl group having 1 to 6 carbon atoms, a halogen group, a hydroxyl group, a carboxyl group, or a trifluoromethyl group.

[0058] Specific examples of W1 include a direct bond, a divalent group represented by the following formula (5), and a divalent group represented by the following formula (6).

[0059] [ka] (R in Equation (6) 61 ~R 68 each independently represents a direct bond or a divalent group represented by the formula (5).

[0060] Examples of diamine components that provide repeating units of general formula (I) in which Y1 is a divalent group having an aromatic ring include p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, 3,3'-dihydroxy-4,4'-diaminobiphenyl, bis(4-amino-3-carboxyphenyl)methane, benzidine, 3,3'-diamino-biphenyl, 2,2'-bis(trifluoromethyl)benzidine, 3,3'-bis(trifluoromethyl)benzidine, m-tolidine, 4,4'-diaminobenzanilide, and 3,4'-diaminobenzanilide. , N,N'-bis(4-aminophenyl)terephthalamide, N,N'-p-phenylenebis(p-aminobenzamide), 4-aminophenoxy-4-diaminobenzoate, bis(4-aminophenyl)terephthalate, biphenyl-4,4'-dicarboxylic acid bis(4-aminophenyl)ester, p-phenylenebis(p-aminobenzoate), bis(4-aminophenyl)-[1,1'-biphenyl]-4,4'-dicarboxylate, [1,1'-biphenyl]-4,4'-diylbis(4-aminobenzoate), 4,4'-oxydi Aniline (also known as 4,4'-diaminodiphenyl ether), 3,4'-oxydianiline, 3,3'-oxydianiline, p-methylenebis(phenylenediamine), 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane nyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, bis(4-aminophenyl)sulfone, 3,3'-bis(trifluoromethyl)benzidine, 3,3'-bis((aminophenoxy)phenyl)propane, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(4-(4-aminophenoxy)diphenyl)sulfone, bis(4-(3-aminophenoxy)diphenyl)sulfone, octafluorobenzidine, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 3,Examples of the compound include 3'-dichloro-4,4'-diaminobiphenyl, 3,3'-difluoro-4,4'-diaminobiphenyl, 2,4-bis(4-aminoanilino)-6-amino-1,3,5-triazine, 2,4-bis(4-aminoanilino)-6-methylamino-1,3,5-triazine, 2,4-bis(4-aminoanilino)-6-ethylamino-1,3,5-triazine, and 2,4-bis(4-aminoanilino)-6-anilino-1,3,5-triazine. Examples of diamine components that provide repeating units of general formula (I) in which Y1 is a divalent group having an aromatic ring containing a fluorine atom include 2,2'-bis(trifluoromethyl)benzidine, 3,3'-bis(trifluoromethyl)benzidine, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, and 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane. Additionally, preferred diamine compounds include 9,9-bis(4-aminophenyl)fluorene, 4,4'-(((9H-fluorene-9,9-diyl)bis([1,1'-biphenyl]-5,2-diyl))bis(oxy))diamine, [1,1':4',1"-terphenyl]-4,4"-diamine, and 4,4'-([1,1'-binaphthalene]-2,2'-diylbis(oxy))diamine. The diamine components may be used alone or in combination.

[0061] Regarding the diamine compound having an alicyclic structure, examples of Y1 which is a group having an alicyclic structure include the following.

[0062] [ka] (In the formula, V1 and V2 each independently represent a direct bond or a divalent organic group, n 21 ~n 26 each independently represents an integer of 0 to 4; R 81 ~R 86are each independently an alkyl group having 1 to 6 carbon atoms, a halogen group, a hydroxyl group, a carboxyl group, or a trifluoromethyl group, and R 91 , R 92 , R 93 are each independently one selected from the group consisting of groups represented by the formula: -CH2-, -CH=CH-, -CH2CH2-, -O-, and -S-.

[0063] Specific examples of V1 and V2 include a direct bond and a divalent group represented by the above formula (5).

[0064] Examples of diamine components that provide repeating units of general formula (I) in which Y1 is a divalent group having an alicyclic structure include 1,4-diaminocyclohexane, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, 1,2-diaminocyclohexane, 1,3-diaminocyclobutane, 1, Examples of the diamine component include 4-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, diaminobicycloheptane, diaminomethylbicycloheptane, diaminooxybicycloheptane, diaminomethyloxybicycloheptane, isophoronediamine, diaminotricyclodecane, diaminomethyltricyclodecane, bis(aminocyclohexyl)methane, bis(aminocyclohexyl)isopropylidene, 6,6'-bis(3-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane, and 6,6'-bis(4-aminophenoxy)-3,3,3',3'-tetramethyl-1,1'-spirobiindane. The diamine component may be used alone or in combination of multiple types.

[0065] <Solvent> Examples of the solvent include aromatic hydrocarbons such as xylene, toluene, and ethylbenzene; aliphatic hydrocarbons such as pentane, hexane, and heptane; non-polar solvents (solvents with a dielectric constant of 6 or less) such as benzoic acid esters such as methyl benzoate, ethyl benzoate, and propyl benzoate; water, methanol, ethanol, acetone, N,N-dimethylformamide, dimethylamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, hexamethylphosphorotriamide, Polar solvents (solvents having a relative dielectric constant of more than 6) such as 1,2-dimethoxymethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl]ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, sulfolane, diphenyl sulfone, tetramethylurea, anisole, m-cresol, phenol, and γ-butyrolactone, and mixtures of these solvents are preferred, with water, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone being particularly preferred.

[0066] <Polyimide binder precursor composition> The polyimide binder precursor composition of the present invention is obtained by reacting a tetracarboxylic acid component with a diamine component in a reaction solvent. This reaction solvent may be any of the above-mentioned solvents, and preferably the reaction solvent is contained as it is in the polyimide binder precursor composition.

[0067] This reaction uses approximately equimolar amounts of a tetracarboxylic acid component (tetracarboxylic dianhydride) and a diamine component, and is carried out at a relatively low temperature, for example, 25° C. or higher and 100° C. or lower, preferably 80° C. or lower. Although not limited thereto, the reaction temperature is usually 25° C. to 100° C., preferably 25° C. to 80° C., more preferably 30° C. to 80° C., and the reaction time is, for example, about 0.1 to 72 hours, preferably about 2 to 60 hours. The reaction can be carried out in an air atmosphere, but is usually suitably carried out in an inert gas atmosphere, preferably a nitrogen gas atmosphere.

[0068] Furthermore, the substantially equimolar amount of the tetracarboxylic acid component (tetracarboxylic dianhydride) and the diamine component specifically means a molar ratio [tetracarboxylic acid component / diamine component] of about 0.90 to 1.10, preferably about 0.95 to 1.05.

[0069] The solid content concentration of the polyimide binder precursor composition (polyimide-equivalent polyimide precursor concentration) is preferably more than 5% by mass to 45% by mass, more preferably more than 10% by mass to 40% by mass, and even more preferably more than 10% by mass to 30% by mass. If the solid content concentration is lower than 5% by mass, the viscosity of the composition becomes too low, and if it is higher than 45% by mass, the composition may lose its fluidity. The reaction solution of the tetracarboxylic acid component and the diamine component may be used as it is as the polyimide binder precursor composition, or the concentration may be adjusted by concentrating or diluting as necessary.

[0070] The solution viscosity (viscosity of the polyimide binder precursor composition) at 30° C. is preferably 1000 Pa·sec or less, more preferably 500 Pa·sec or less, further preferably 300 Pa·sec or less, and particularly preferably 200 Pa·sec or less. A solution viscosity of 1000 Pa·sec or less is preferable because it facilitates mixing of the electrode active material powder and uniform application onto the current collector.

[0071] The polyimide binder precursor composition may contain additives other than the electrode active material, which will be described in the next section "Electrode Mixture Paste". Details will be described later using a lithium ion secondary battery as an example.

[0072] <Electrode mixture paste> The electrode mixture paste, which is one embodiment of the present invention, is a composition containing a polyimide binder precursor composition, an electrode active material, and an optionally added solvent.

[0073] The electrode active material that can be used in the electrode mixture paste of the present invention can be suitably a known one. The polyimide binder precursor composition of the present invention can be used in either the negative electrode or the positive electrode. Therefore, the electrode active material may be either the negative electrode active material or the positive electrode active material. Usually, the effect of using the polyimide binder precursor composition of the present invention is greater in the negative electrode. In this case, the electrode active material includes a negative electrode active material. As the electrode active material, for example, lithium-containing metal composite oxide, carbon powder, silicon powder, tin powder, or alloy powder containing silicon or tin is preferable. The amount of the electrode active material in the electrode mixture paste is not particularly limited, and may be appropriately determined according to the desired capacity. Usually, the amount of the electrode active material is preferably 0.1 times or more, more preferably 1 time or more, even more preferably 5 times or more, and even more preferably 10 times or more, based on the solid content (polyimide equivalent mass) in the polyimide binder precursor composition, on a mass basis. Within these ranges, the active portion in the negative electrode active material layer increases, so that the electrode can function sufficiently. On the other hand, in order to effectively prevent the electrode active material from falling off by sufficiently binding it to the current collector, the amount of the electrode active material is usually preferably 1000 times or less the solid content in the polyimide binder precursor composition.

[0074] Examples of the negative electrode active material for lithium ion secondary batteries include lithium metal, lithium alloys, and carbon materials capable of absorbing and releasing lithium (e.g., graphitizable carbon, non-graphitizable carbon with a (002) plane spacing of 0.37 nm or more, and graphite with a (002) plane spacing of 0.34 nm or less), tin (single element), tin compounds, silicon (single element), silicon compounds, and Li4Ti5O 12 Lithium titanate compounds such as tin (single element), tin compounds, silicon (single element), or silicon compounds can be used alone or in combination. In the present invention, the negative electrode active material preferably contains at least a silicon-containing material such as tin (single element), tin compounds, silicon (single element), or silicon compounds (hereinafter, sometimes referred to as silicon-containing negative electrode active material or silicon-containing active material). In particular, silicon-containing materials such as silicon (single element) or silicon compounds have a theoretical capacity that is extremely large compared to graphite, but also have a very large volume expansion rate of the electrode active material itself during charging.

[0075] The lithium-ion secondary battery using the polyimide binder precursor composition of the present invention suppresses the deterioration of the electrode active material due to volume expansion, and is excellent in characteristics during use such as cycle characteristics, as well as characteristics in a wide temperature range such as low-temperature characteristics and gas generation after high-temperature storage.

[0076] The type of the silicon-containing active material is not particularly limited, and examples thereof include silicon (single substance), silicon compounds, silicon partial substituents, silicon compound partial substituents, solid solutions of silicon compounds, and the like. Specific examples of the silicon compound include silicon oxides represented by SiOx (0.05 < x < 1.95), silicon carbides represented by the formula: SiCy (0 < y < 1), silicon nitrides represented by the formula: SiNz (0 < z < 4 / 3), and silicon alloys which are alloys of silicon and a different element M. In the silicon alloy, as the different element M1, at least one element selected from the group consisting of Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, and Ti is preferably exemplified.

[0077] In addition, the silicon partial substituent is a compound in which a part of the silicon contained in silicon (single substance) and the silicon compound is substituted with a different element M2. Specific examples of the different element M2 include, for example, B, Mg, Ni, Ti, Mo, Co, Ca, Cr, Cu, Fe, Mn, Nb, Ta, V, W, Zn, C, N, and Sn. Among these silicon-containing substances, silicon (single substance), silicon oxide, or a silicon alloy is preferable, and silicon (single substance) or silicon oxide is more preferable.

[0078] Regarding the amount of the silicon-containing active material, as the mass of the net silicon in the negative electrode binder, in order to increase the capacity, 1% by mass or more is preferable, 5% by mass or more is more preferable, 10% by mass or more is still more preferable, and from the viewpoint of improving the cycle characteristics, 95% by mass or less is preferable, 65% by mass or less is more preferable, and 45% by mass or less is still more preferable.

[0079] Solvents that can be used in the electrode mixture paste include aromatic hydrocarbons such as xylene, toluene, and ethylbenzene, aliphatic hydrocarbons such as pentane, hexane, and heptane, non-polar solvents such as benzoic acid esters such as methyl benzoate, ethyl benzoate, and propyl benzoate, water, methanol, ethanol, acetone, N,N-dimethylformamide, dimethylamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N-methylcaprolactam, hexamethylcaprolactam, and methyl ketone. Methyl phosphorotriamide, 1,2-dimethoxymethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, tetrahydrofuran, bis[2-(2-methoxyethoxy)ethyl]ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, sulfolane, diphenyl sulfone, tetramethylurea, anisole, m-cresol, phenol, and γ-butyrolactone are preferred, and water, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactone are particularly preferred.

[0080] The solvent may be the same as that in the polyimide binder precursor composition, or may be concentrated as necessary or additional solvent may be added to the composition to obtain a suitable concentration for application.

[0081] In the electrode mixture paste of the present invention, when the solvent system is an aqueous solvent system, it is preferable to contain a pyridine compound and an imidazole compound. This can reduce the swelling degree of the obtained polyimide in the electrolyte solution, and increase the elongation rate (elongation at break) and the breaking energy. In addition, the heat treatment temperature for obtaining the negative electrode active material layer can be kept low. The pyridine compound is a compound having a pyridine skeleton in its chemical structure, and suitable examples thereof include pyridine, 3-pyridinol, quinoline, isoquinoline, quinoxaline, 6-tert-butylquinoline, acridine, 6-quinolinecarboxylic acid, 3,4-lutidine, and pyridazine. These pyridine compounds may be used alone or in combination. Examples of the imidazole compound include 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 4-ethyl-2-methylimidazole, and 1-methyl-4-ethylimidazole. The imidazole used may be one type or a mixture of two or more types.

[0082] The amount of the pyridine compound is not limited, but is preferably 0.05 to 2.0 molar equivalents, more preferably 0.1 to 1.0 molar equivalents, relative to 1 mole of the repeating unit of the polyimide precursor (particularly polyamic acid). If the amount added is outside this range, it may be difficult to make the solvent system water-based. The amount of the imidazole compound is not limited, but is 1.6 molar equivalents or more, more preferably 2.0 molar equivalents or more, and even more preferably 2.4 molar equivalents or more, relative to 1 mole of the amic acid repeating unit of the polyamic acid.

[0083] The electrode mixture paste of the present invention may contain known additives as necessary, such as a negative electrode conductive agent, a base, a surfactant, a viscosity modifier, a conductive auxiliary, a silane coupling agent, and a binder other than polyimide, which may be used within a range that does not impair the effects of the present invention.

[0084] The negative electrode conductive agent is not particularly limited as long as it is an electronic conductive material that does not undergo chemical changes, but it is preferable to use metal powder such as copper, nickel, titanium, or aluminum, or a carbon material, etc. Suitable examples of carbon materials used as the conductive agent or negative electrode active material include graphite such as natural graphite (e.g., flake graphite) and artificial graphite; one or more types of carbon black selected from acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; and fibrous carbon powder such as carbon nanotubes and carbon fibers.

[0085] It is more preferable to use a suitable mixture of graphite and carbon black, graphite and fibrous carbon powder, or carbon black and fibrous carbon powder as the negative electrode conductive agent. In particular, the use of fibrous carbon powder is preferable because it ensures electrical conductivity and therefore requires less use of a conductive agent with a large specific surface area. Carbon materials are used as conductive agents or negative electrode active materials, and the amount of the carbon material added to the negative electrode mixture is preferably 1 to 90% by mass, more preferably 10 to 70% by mass.

[0086] When a carbon material is used as a negative electrode conductive agent by mixing it with a silicon-containing negative electrode active material, the ratio of the silicon-containing negative electrode active material to the carbon material is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the net silicon of the silicon-containing negative electrode active material in the negative electrode mixture, from the viewpoint of cycle improvement based on the effect of improving electronic conductivity by mixing with the carbon material. In addition, if the ratio of the carbon material mixed with the silicon-containing negative electrode active material is too high, the amount of the silicon-containing negative electrode active material in the negative electrode mixture layer decreases, and there is a risk that the effect of increasing capacity is reduced. Therefore, the net mass of silicon of the silicon-containing negative electrode active material is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 5% by mass or more, based on the total mass of the carbon material. In addition, it is more preferable that the conductive agent is a composite obtained by mixing it with the silicon-containing active material in advance and appropriately heat-treating it.

[0087] When graphite is used, it is more preferable to use a carbon material having a graphite type crystal structure in which the lattice spacing (d002) of the graphite lattice plane (002) is 0.340 nm (nanometers) or less, particularly 0.335 to 0.337 nm. In particular, it is preferable to use artificial graphite particles having a block structure in which a plurality of flat graphitic fine particles are aggregated or bonded in a non-parallel manner, or particles obtained by repeatedly applying mechanical actions such as compression force, friction force, and shear force to spheroidize scaly natural graphite.

[0088] The density of the negative electrode, excluding the current collector, is 1.5 g / cm 3 When the negative electrode sheet is pressed to a density of 1000 or more, the ratio I(110) / I(004) of the peak intensity I(110) of the (110) plane of the graphite crystals to the peak intensity I(004) of the (004) plane obtained by X-ray diffraction measurement of the negative electrode sheet is preferably 0.01 or more, since the electrochemical characteristics are improved over a wider temperature range, more preferably 0.05 or more, and even more preferably 0.1 or more. In addition, since excessive processing may reduce the crystallinity and reduce the discharge capacity of the battery, the upper limit of the peak intensity ratio I(110) / I(004) is preferably 0.5 or less, more preferably 0.3 or less.

[0089] In addition, it is preferable that the highly crystalline carbon material (core material) is coated with a carbon material having a lower crystallinity than the core material, since the electrochemical properties over a wide temperature range are further improved. The crystallinity of the carbon material of the coating can be confirmed by TEM. When a highly crystalline carbon material is used, it reacts with the non-aqueous electrolyte during charging, and the interface resistance increases, which tends to deteriorate the properties of the lithium ion secondary battery over a wide temperature range, such as low-temperature properties after high-temperature storage and gas generation, but when the polyimide binder precursor composition according to the present invention is used, the properties of the lithium ion secondary battery are improved.

[0090] The negative electrode mixture paste contains the polyimide binder precursor composition of the present invention, and may contain other binders in an amount of 95% by mass or less, preferably 45% by mass or less.

[0091] Examples of binders other than the polyimide binder precursor composition of the present invention include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, butadiene rubber, nitrile rubber, polyacrylonitrile, ethylene-vinyl alcohol copolymer resin, ethylene-propylene-diene rubber, polyurethane, polyacrylic acid, polyamide, polyacrylate, polyvinyl ether, fluororubber, carboxymethylcellulose, and sodium carboxymethylcellulose.

[0092] The electrode mixture paste of the present invention may further contain a solid electrolyte. The solid electrolyte may be, for example, La2O3 having a perovskite crystal structure. 0.51 Li 0.34 TiO 2.94 , garnet-type crystal Li7La3Zr2O 12 , NASICON type crystal Li 1.3 Al 0.3 Ti 1.7 (PO4)3, amorphous LIPON(Li 2.9 PO 3.3 N 0.46 ) and sulfide-based solid electrolytes such as Li2S-SiS2 and Li2S-P2S5.

[0093] The electrode mixture paste of the present invention can be produced as a uniform composition by applying a known production method to the above-mentioned components, and adding, stirring, mixing, etc. For example, the electrode mixture paste may be produced by producing a solution or dispersion liquid by mixing a polyimide-based binder with a solvent, and then adding and mixing various additives.

[0094] <Negative electrode active material layer, negative electrode sheet> The negative electrode mixture paste of the present invention is cast or applied on a conductive current collector, and the paste is heated to remove the solvent, and then imidized as necessary to form a negative electrode (negative electrode sheet) having a negative electrode active material layer on the current collector. During the process of forming the negative electrode sheet, it is also preferable to press the negative electrode sheet using a roll press until the desired electrode density is achieved. Any known current collector can be used.

[0095] The polyimide precursor present in the polyimide binder precursor composition is converted to a polyimide binder by heat treatment, and particles such as active material and conductive agent are bound to each other and to the current collector at the same time. The heat treatment removes the solvent, and the imidization of the polyimide precursor proceeds, so that the solubility in solvents such as electrolytes decreases and the solvent resistance improves. The heat treatment can be carried out at, for example, 80°C to 450°C. To proceed with imidization, it is preferable to heat the material so that the maximum temperature is preferably 180°C to 450°C, more preferably 200°C to 450°C, for example, 250°C to 380°C or higher. In the temperature range of 200°C or less, particularly 180°C or less, the solvent mainly proceeds. Therefore, the heat treatment may be carried out stepwise or continuously by dividing the step of mainly removing the solvent from the step of mainly proceeding with imidization into step 1 in which heating is performed at 80°C to 200°C (or 180°C) and step 2 in which heating is performed at a temperature of 200°C or higher (or 180°C or higher). In practice, imidization may proceed at higher temperatures in step 1, and solvent removal may also occur in step 2 depending on the degree of solvent removal in step 1.

[0096] The times of steps 1 and 2 can be appropriately determined in consideration of the simplicity of the process, the desired imidization rate, etc. The time of step 1 may be 0 seconds (when step 1 is not performed), but is preferably 1 minute or more, more preferably 10 minutes or more, and preferably 5 hours or less, more preferably 2 hours or less, while the time of step 2 is preferably 10 minutes or more, more preferably 30 minutes or more, and preferably 24 hours or less, more preferably 12 hours or less.

[0097] When the imidization rate of the polyimide precursor present in the polyimide binder precursor composition is high, for example, when the imidization rate is 70% or more, preferably 80% or more (90% or more, or even 100%), the heat treatment may be limited to the above-mentioned step 1 for mainly removing the solvent. However, in order to ensure the removal of the solvent and / or to increase the imidization rate, the above-mentioned step 2 may also be carried out.

[0098] The thickness of the negative electrode active material layer of the present invention may be appropriately determined depending on the application and the desired capacity. Although not limited, it is preferable to use it in the range of 0.1 μm to 500 μm, for example. It is more preferable to use it in the range of 1 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, more preferably 300 μm or less, even more preferably 100 μm or less, and even more preferably 50 μm or less.

[0099] <Cathode active material> As the positive electrode active material for lithium secondary batteries, a composite metal oxide containing one or more selected from cobalt, manganese, and nickel and lithium is used. These positive electrode active materials can be used alone or in combination of two or more. Examples of such lithium composite metal oxides include LiCoO2, LiMn2O4, LiNiO2, and LiCo 1-x Ni x O2(0.01 <x<1)、LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 3 / 2 O4 and LiCo 0.98 Mg 0.02 LiCoO2 and LiMn2O4, LiCoO2 and LiNiO2, or LiMn2O4 and LiNiO2 may be used in combination.

[0100] In addition, a part of the lithium composite metal oxide may be replaced with other elements in order to improve safety and cycle characteristics during overcharging, and to enable use at a charging potential of 4.3 V or higher. For example, a part of the cobalt, manganese, and nickel may be replaced with at least one element such as Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn, Cu, Bi, Mo, and La, a part of the O may be replaced with S or F, or the lithium composite metal oxide may be coated with a compound containing these other elements. Among these, lithium composite metal oxides such as LiCoO2, LiMn2O4, and LiNiO2, which can be used at a positive electrode charge potential of 4.3 V or more based on Li in a fully charged state, are preferred. 1-x M x Lithium cobalt oxide substituted with different elements such as LiNiO2 (wherein M is one or more elements selected from Sn, Mg, Fe, Ti, Al, Zr, Cr, V, Ga, Zn, and Cu, and 0.001≦x≦0.05) 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 1 / 2 Mn 3 / 2 Lithium composite metal oxides that can be used at 4.4 V or higher, such as lithium composite metal oxides in which the ratio of nickel atoms and manganese atoms to all metal elements other than lithium atoms is 50 atomic % or more and 100 atomic % or less, such as a solid solution of Li2MnO3 and LiMO2 (M is a transition metal such as Co, Ni, Mn, or Fe), are 50 atomic % or more and 100 atomic % or less. When a lithium composite metal oxide that operates at a high charging voltage is used, the characteristics of the lithium ion secondary battery tend to deteriorate when used over a wide temperature range due to a reaction with the electrolyte during charging, but the use of the polyimide binder precursor composition according to the present invention can suppress the deterioration of the characteristics of these lithium ion secondary batteries.

[0101] Furthermore, a lithium-containing olivine-type phosphate can be used as the positive electrode active material. In particular, a lithium-containing olivine-type phosphate containing one or more selected from iron, cobalt, nickel, and manganese is preferable. Specific examples thereof include one or more selected from LiFePO4, LiCoPO4, LiNiPO4, and LiMnPO4. These lithium-containing olivine-type phosphates may be partially substituted with other elements, and part of the iron, cobalt, nickel, and manganese may be substituted with one or more elements selected from Co, Mn, Ni, Mg, Al, B, Ti, V, Nb, Cu, Zn, Mo, Ca, Sr, W, and Zr, or may be coated with a compound or carbon material containing these other elements. Of these, LiFePO4 or LiMnPO4 is preferred. The lithium-containing olivine-type phosphate can also be used by mixing with, for example, the above-mentioned positive electrode active material.

[0102] <Positive electrode conductive material> The conductive agent for the positive electrode is not particularly limited as long as it is an electron conductive material that does not undergo chemical changes. For example, graphite such as natural graphite (e.g., flake graphite), artificial graphite, one or more carbon blacks selected from acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and fibrous carbon powder such as carbon nanotubes and carbon fibers are preferably used. In addition, it is more preferable to use a suitable mixture such as graphite and carbon black, graphite and fibrous carbon powder, or carbon black and fibrous carbon powder. The amount of the conductive agent added to the positive electrode mixture is preferably 1 to 10 mass%, and particularly preferably 2 to 5 mass%.

[0103] <Positive electrode binder> The polyimide binder precursor composition of the present invention can be used for the positive electrode mixture paste, but other binders such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene-butadiene copolymer (SBR), acrylonitrile-butadiene copolymer (NBR), carboxymethyl cellulose (CMC), or ethylene propylene diene terpolymer can also be used. The polyimide binder precursor composition of the present invention can be used in combination with other binders, and the preferred embodiments in this case are the same as those described in the negative electrode binder section.

[0104] <Positive electrode sheet> The positive electrode sheet is obtained by casting or coating an electrode mixture paste, which is a mixture of a positive electrode binder, a positive electrode active material, and any other components such as a conductive agent, onto a current collector to form an active material layer.

[0105] <Lithium-ion secondary battery> The lithium ion secondary battery according to one embodiment of the present invention includes the above-mentioned negative electrode (negative electrode sheet), and the positive electrode (positive electrode sheet), electrolyte, and other components such as a separator, etc., which are provided as necessary, may adopt known components required for lithium ion secondary batteries. In addition, this lithium ion secondary battery may be a lithium polymer battery using a gel electrolyte as the electrolyte, or an all-solid-state battery using an inorganic solid electrolyte such as an oxide or sulfide system.

[0106] <Other power storage devices> The polyimide binder of the present invention can be used not only in lithium ion secondary batteries, but also in other electricity storage devices having a mechanism similar to that of lithium ion secondary batteries, such as lithium ion capacitors. EXAMPLES

[0107] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0108] The abbreviations of the compounds used in the following examples are explained below. <Tetracarboxylic acids> H”-PMDA: Cyclohexane-1,2,4,5-tetracarboxylic dianhydride (chair isomer) H'-PMDA: Cyclohexane-1,2,4,5-tetracarboxylic dianhydride (boat isomer) CBDA: 1,2,3,4-cyclobutanetetracarboxylic dianhydride CpODA: Norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane 5,5'',6,6''-tetracarboxylic dianhydride DNDAxx: (4arH,8acH)-decahydro-1t,4t:5c,8c-dimethanonaphthalene-2t,3t,6c,7c-tetracarboxylic dianhydride BTA: Bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride H-sBPDA: [1,1'-bi(cyclohexane)]-3,3',4,4'-tetracarboxylic dianhydride PPHT: (Octahydro-1,3-dioxo-5-isobenzofurancarboxylic acid) 1,4-phenylenediamide PMDA: Pyromellitic dianhydride s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0109] <Diamines> ODA: 4,4'-diaminodiphenyl ether PPD: p-phenylenediamine TPE-R: 1,3-bis(4-aminophenoxy)benzene BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane MBAA: Bis(4-amino-3-carboxyphenyl)methane DABAN: 4,4'-diaminobenzanilide DATP: 4,4”-diamino-p-terphenyl

[0110] <Other> EC: Ethylene carbonate DEC: Diethyl carbonate VC: Vinylene carbonate NMP: N-methyl-2-pyrrolidone

[0111] [Table 1]

[0112] <Calculation of irreversible capacity of polyimide binder> (A1) Preparation of negative electrode for evaluation Graphite (MAG-D; massive artificial graphite, manufactured by Showa Denko Materials Co., Ltd., average particle size 20 μm) was mixed as a negative electrode active material with a polyimide binder precursor composition (Examples and Comparative Examples) in solid content ratios of 92:8, 95:5, and 97:3 (mass%), and NMP was added and mixed to give a slurry concentration of approximately 50 mass%, thereby preparing a negative electrode mixture paste.

[0113] The negative electrode mixture paste was applied onto a nickel-plated steel foil (thickness 10 μm) as a current collector and pre-dried on a hot plate at 110 °C for 3 minutes. It was then roll-pressed and placed in an electric furnace for heat treatment at 360 °C for 1.5 hours under argon flow to obtain a negative electrode for evaluation (2 mAh / cm 2 ) was prepared.

[0114] (A2) Preparation of evaluation battery Using the negative electrode for evaluation obtained in (1) above, a battery for evaluation was fabricated in the following configuration. Cell shape: 2032 type coin cell Counter electrode: Lithium foil (metallic lithium) ·Electrolyte: 1M LiPF6 / EC:DEC=1:1 (volume%) VC1 mass% addition Separator

[0115] (A3) Battery evaluation Charge and discharge were carried out under the following conditions. ·Measurement temperature: 30℃ Charge / discharge range: 0.001~2.0V (However, the first charge should be done from the natural potential (approximately 3V) to 0.001V.) Charge / discharge current value: 0.02C The charge capacity and discharge capacity (mAh / g) were calculated based on the weight of the entire active material layer (the sum of the weight of the active material and the weight of the binder), and the difference between the first charge capacity and the first discharge capacity up to 1 V was calculated as the irreversible capacity. Note that here, the absorption of Li into the "negative electrode for evaluation" is referred to as "charging," and the release of Li from the "negative electrode for evaluation" is referred to as "discharging."

[0116] (A4) Calculation of irreversible capacity of polyimide binder itself As shown in Figure 1, the irreversible capacity of the battery calculated in (A3) above was plotted against the amount of polyimide binder added (mass%) to create a calibration curve. In the resulting calibration curve, the irreversible capacity at a binder addition amount of 100% was taken as the irreversible capacity of the polyimide itself.

[0117] <Evaluation of silicon-based anodes using polyimide binder> (B1) Preparation of silicon-based negative electrode A negative electrode mixture paste was prepared by mixing silicon (manufactured by Elkem, average particle size 3 μm) as the negative electrode active material, a polyimide binder precursor composition (Examples and Comparative Examples), and a conductive assistant (acetylene black manufactured by DENKA) in a solid content ratio of 60:30:10 (mass %). The negative electrode mixture paste was applied onto a nickel-plated steel foil (thickness 10 μm) as a current collector, and pre-dried at 110°C for 3 minutes. It was then roll-pressed and placed in an electric furnace for heat treatment at 360°C for 1.5 hours under argon flow to obtain a negative electrode (3 mAh / cm 2 ) was prepared.

[0118] (B2) Battery evaluation using silicon-based anode A battery was prepared in the same manner as in (A2) above, and charged and discharged under the following conditions. ·Measurement temperature: 30℃ Charge / discharge range: 0.001~1.0V (However, the first charge should be done from the natural potential (approximately 3V) to 0.001V.) Charge / discharge current value: 0.1C (B3) Initial charge / discharge efficiency The initial charge / discharge efficiency was calculated by the following formula. Initial charge / discharge efficiency = (first discharge capacity up to 1V) / (first charge capacity) x 100%

[0119] <Evaluation of mechanical properties of polyimide binder> The polyimide binder precursor composition (Examples and Comparative Examples) was applied onto a glass substrate using a spin coater, dried at 80°C for 10 minutes, and then heat-treated in a nitrogen atmosphere at 120°C for 30 minutes, 150°C for 10 minutes, 200°C for 10 minutes, 250°C for 10 minutes, and 350°C for 10 minutes (heating rate 5°C / min) to obtain a film with a thickness of 10 μm. The obtained film was cut into a strip of 10 mm width and 200 mm length to prepare a test sample. The test sample was set in a tensile testing machine with the chuck distance set to 100 mm, and the sample was pulled at a speed of 50 mm / min. The elastic modulus, elongation (elongation at break), and breaking energy were calculated from the obtained stress-strain curve. The measurement environment was room temperature and in air.

[0120] <Production Examples and Comparative Examples of Polyimide Binder Precursor Composition> [Composition PI-1] 160 g of NMP was added to a reaction vessel, and the inside of the vessel was replaced with nitrogen and kept at 50°C. 23.5916 g of ODA was added and dissolved therein, and then 26.3424 g of H″-PMDA (molar ratio to diamine: 1) was added stepwise together with 40 g of NMP, and the mixture was stirred overnight at 50°C to obtain a polyimide binder precursor composition PI-1. Viscosity 49P

[0121] [Composition PI-2~PI-12] Polyimide binder precursor compositions PI-2 to PI-12 were obtained by reacting in the same manner as composition PI-1 using the tetracarboxylic dianhydrides and diamines shown in Table 2. The viscosities and concentrations are shown in Table 2.

[0122] [Composition PI-10'] (Polyimide solution-type composition) A polyimide solution-type polyimide binder precursor composition was produced by imidization from the same monomer composition as composition PI-10. First, 160 g of NMP was added to a reaction vessel, and the vessel was replaced with nitrogen and kept at 50°C. 32.3399 g of BAPP was added and dissolved therein, and the temperature of the reaction bath was then raised to 70°C, and 17.6601 g of H''-PMDA (molar ratio of 1 to diamine) was added stepwise together with 40 g of NMP. After stirring for 30 minutes at 70°C, the mixture was stirred at 170°C for 3 hours for imidization to obtain a polyimide binder precursor composition PI-10'. The viscosity and concentration are shown in Table 2.

[0123] [Compositions PI-13 to PI-14] (copolymerized polyimide precursors) Polyimide binder precursor compositions PI-13 and PI-14 were obtained by using two types of tetracarboxylic dianhydrides shown in Table 2 as the tetracarboxylic acid components and diamines shown in Table 2 in the same manner as in composition PI-1, and reacting in the same manner as in composition PI-1. The viscosity and concentration are shown in Table 2. For compositions using two or more compounds as the tetracarboxylic acid components and diamine components, the molar ratio is shown in parentheses after the monomers.

[0124] [Composition PI-15~PI-18] The tetracarboxylic dianhydrides and diamines shown in Table 2 were used and reacted in the same manner as in composition PI-1 to obtain polyimide binder precursor compositions PI-15 to PI-18.

[0125] [Composition PI-MIX] (Blend of polyimide precursors) As shown in Table 2, two types of polyimide binder precursor compositions were blended to obtain a polyimide binder precursor composition PI-MIX. The viscosity and concentration are shown in Table 2. In Table 2, the mixing ratio is shown in parentheses as a molar ratio (ratio of the total number of monomer units).

[0126] [Composition PI-19~PI-23] Polyimide binder precursor compositions PI-19 to PI-23 were obtained by reacting the tetracarboxylic dianhydrides and diamines shown in Table 2 in the same manner as in composition PI-1. The viscosities and concentrations are shown in Table 2.

[0127] [Table 2]

[0128] <Polyimide binder evaluation results> Using the produced polyimide binder precursor composition, an evaluation battery was produced according to <Calculation of irreversible capacity of polyimide binder>, and the battery was evaluated to prepare a calibration curve and calculate the irreversible capacity of the polyimide binder. The results are shown in Table 3.

[0129] <Evaluation results of silicon-based anode using polyimide binder> Using the prepared polyimide binder precursor composition, a negative electrode using silicon as the negative electrode active material was prepared according to <Evaluation of silicon simple substance negative electrode using polyimide binder>, a battery was prepared, and the initial charge-discharge efficiency was evaluated. The results are shown in Table 3.

[0130] [Table 3]

[0131] From Table 3, it was found that when the irreversible capacity of the polyimide binder is 1200mAh / g or less, the initial charge-discharge efficiency of the battery using silicon as the negative electrode active material is 80% or more. Therefore, by using the polyimide binder precursor composition of the present invention, it is possible to increase the capacity of the lithium ion secondary battery.

[0132] <Evaluation results of mechanical properties of polyimide binder> Using the produced polyimide binder precursor composition, the mechanical properties (elastic modulus, elongation (elongation at break), and breaking energy) of the binder were measured according to <Evaluation of mechanical properties of polyimide binder>. The results are shown in Table 4. The results show that the polyimide binder obtained from the polyimide binder precursor composition of the present invention has excellent mechanical properties and can fully function as a binder.

[0133] [Table 4] [Industrial Applicability]

[0134] The present invention can be suitably applied as an electrode binder for an electricity storage device such as a lithium ion secondary battery.

Claims

1. A polyimide binder precursor composition for an electrode of an electrical storage device, comprising: a reaction product of a tetracarboxylic acid component and a diamine component; and a solvent, A polyimide binder obtained from the polyimide binder precursor composition has an irreversible capacity of 1200 mAh / g or less.

2. 2. The polyimide binder precursor composition of claim 1, wherein the polyimide binder precursor composition comprises a reaction product of a tetracarboxylic acid component containing 50 mol % or more of an alicyclic tetracarboxylic dianhydride and a diamine component, and a solvent.

3. The polyimide binder precursor composition of claim 1 , wherein the diamine component contains 50 mol % or more of an aromatic diamine compound.

4. A negative electrode mixture paste for an electrical storage device, comprising the polyimide binder precursor composition according to claim 1 and an active material containing a silicon-containing material and / or graphite.

5. (a) an active material comprising a silicon-containing material and / or graphite; and A heat product of the polyimide precursor contained in the polyimide binder precursor composition according to any one of claims 1 to 3, comprising a polyimide binder that binds the active material. A negative electrode active material layer containing (b) Current collector A negative electrode for an electricity storage device comprising:

6. An electricity storage device comprising the electricity storage device negative electrode according to claim 5 .

7. A step of casting or applying the negative electrode mixture paste according to claim 4 onto a current collector; A process of heating the applied layer of negative electrode mixture paste to form a negative electrode active material layer. The method for producing a negative electrode for an electricity storage device comprising the steps of:

8. A method for producing an electricity storage device, comprising the method for producing a negative electrode according to claim 7 as one step.

Citation Information

Patent Citations

  • Negative electrode active material for lithium ion secondary battery, and method for manufacturing the same

    JP2016066579A

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery using the same

    JP2019003873A

  • Polyimide electrode binders

    US20060099506A1

  • Composition of aqueous polyimide precursor solution and method for producing composition of aqueous polyimide precursor solution

    WO2013035806A1

  • Polyimide precursor and polyimide

    WO2014208704A1